HOW MEANINGFUL WORK REDUCES TURNOVER INTENTION THROUGH WORK ENGAGEMENT AMONG GENERATION Z - Zahra Arridhani Siregar; Rahmi Lubis; Patisina (Pena Cendekia Insani, 2026)
The increasing phenomenon of turnover intention among Generation Z in Indonesia poses a challenge for organizations in retaining young and potential employees. This generation is known to be adaptive and critical, and to place work meaningfulness as an important factor in job satisfaction and organizational loyalty. This study aims to analyze the effect of meaningful work on turnover intention, with work engagement as a mediating variable among Generation Z employees in Indonesia. This research employed a quantitative explanatory approach using a survey method. The sample consisted of 387 respondents, determined based on the Krejcie and Morgan table through convenience sampling. The research instruments included the Meaningful Work Scale adapted from Steger, Dik, and Duffy (2012), the Work Engagement Scale (UWES) from Schaufeli and Bakker (2004), and the Turnover Intention Scale from Bothma and Roodt (2013). Data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS 4.0. The results indicate that meaningful work has a negative and significant effect on turnover intention (? = -0.19; p = 0.022) and a positive and significant effect on work engagement (? = 0.77; p = 0.000). Furthermore, work engagement has a negative and significant effect on turnover intention (? = -0.249; p = 0.002) and mediates the relationship between meaningful work and turnover intention (? = -0.192; p = 0.002). These findings highlight the importance of creating a meaningful work environment to enhance engagement and reduce turnover intention among Generation Z employees.